An integrative pharmacology-based study on the pharmacological activity and mechanism of xiaoji-chenpi formula (XCF) against MAFLD - Liang, Shufei; Dong, Yang; Chang, Zukang; Guo, Pingping; Jia, Jinghan; Yang, Gangao; Chen, Yongning; Dong, Ling; Xu, Xiaoxue; Cai, Tianqi; Li, Tianxing; Fang, Yini; et al. (Frontiers in Pharmacology, 2025)
Metabolic-associated fatty liver disease (MAFLD) is a common chronic metabolic disease worldwide that seriously threatens human health. The Xiaoji-chenpi formula (XCF), derived from QingGanSan (QGS), has previously been proven to be clinically effective in MAFLD. However, its pharmacological activity and mechanism have not been studied in depth. In this study, we explored and determined the optimal amounts of cholesterol and fat additives (4% and 20%, respectively) for the modeling of zebrafish MAFLD via orthogonal tests. The zebrafish MAFLD model was used for preliminary screening and determination of the pharmacological activity of XCF on MAFLD. XCF significantly reduced the body mass index (BMI), improved the morphology of liver cells and reduced the number of lipid vacuoles, which were better than the corresponding pharmacological activity of silymarin and resveratrol in zebrafish with MAFLD. The four main active compounds in XCF were identified by HPLC analysis as chlorogenic acid, naringin, hesperidin and quercetin. MAFLD in the mouse model was induced by a high-fat diet (HFD), and the pharmacological activity and mechanism of XCF were investigated by measuring plasma and hepatic physiological indices. XCF reduced the plasma TC and TG levels, reduced the liver TC and TG levels, and relieved liver lipid accumulation and inflammation in the mice. Key differentially expressed genes were identified through transcriptomics and detected via western blotting. XCF regulated the levels of INSIG1, SREBP1, FASN, ACC, SPP1, LGALS3, TNF-α and IL-1β in the livers of the MAFLD mice and improved the disease status. Our research provides a basis for developing an effective functional product for treating the occurrence and progression of MAFLD.